The Eﬃcacy of a Peptide Product from the Pituitary Gland of Rangifer tarandus as an Antioxidant Agent Under the Combined Eﬀects of Light Desynchronosis and Depriming Toxicant - E. G. Batotsyrenova; V. A. Kashuro; A. V. Sharabanov; V. K. Kozlov; A. L. Kovalenko (Антибиотики и Химиотерапия)
The possibility of using methods for determining the oxidative status of an organism (enzymatic and non-enzymatic links of the cellular antioxidant system) to assess the antioxidant properties of peptides of the pituitary gland of the reindeer (Rangifer tarandus) were investigated in an experimental study conducted with a combined eﬀect of factors of diﬀerent nature on rats: a physical factor — prolonged light desynchronosis (diﬀerent light modes) and a chemical factor - acute severe poisoning with depriving toxicant (sodium thiopental, LD50). The pharmacological correction of the oxidative status of cells in the animals of the experimental subgroups was carried out with the peptide product of the pituitary gland, intranasally injecting the surviving rats with the bioproduct at a dose of 100 µg/kg, once in the ﬁrst half of the objective day for 14 days after poisoning with sodium thiopental. The surviving animals of the control groups were similarly injected with saline. The eﬀectiveness of the correction of the disruptions of the cellular oxidative status with the peptide product of the pituitary gland was tested 30 days after the onset of the combined eﬀect of stress factors on rats. It was found that the use of this bioactive peptide product in experimental animals exposed to diﬀerent light modes and a chemical factor contributed to a decrease in the initially increased indicators of lipid peroxidation in rat erythrocytes and an increase in the initially reduced indicators of the enzymatic link of antioxidant protection. The activity of superoxide dismutase, glutathione peroxidase, glutathione transferase, as well as glucose-6-phosphate dehydrogenase increased after pharmacological correction. The concentration of reduced glutathione also increased in erythrocytes. The maximum changes were observed in the experimental subgroup of rats exposed to the combined eﬀects of constant illumination and depriming toxicant. It was also found that the revealed positive changes in the indicators of the enzymatic link of antioxidant protection in animals of the experimental subgroups are associated with the maintenance of a suﬃcient concentration of reduced glutathione in red blood cells, which contributed to the maintenance of the cellular redox balance, when the conditions of the external lighting regime are violated.